Developing a simple, cost-effective proof-of-concept vaccine candidate against EHEC for cattle - Cecilia M. Duarte; Laura A. Basile; Diego G. Noseda; Pierina Fasolo; Pilar Leguiza; Mara S. Roset; Gabriel Briones (PLoS ONE, 2026)
Enterohemorrhagic Escherichia coli (EHEC) is a zoonotic pathogen responsible for severe human diseases, including hemorrhagic diarrhea and hemolytic uremic syndrome (HUS), primarily mediated by Shiga toxins (Stx). Intestinal colonization depends on the type III secretion system (T3SS), which induces attaching and effacing (A/E) lesions. Cattle are the main reservoir, and preharvest vaccines are key to reducing human exposure. In this work, we engineered a chimeric antigen EIT (EspA 36-192 -Intimin 653-935 -Tir 258-361 ) to be expressed in the periplasm of E. coli BL21, enabling simple extraction by thermal shock. To favor scalable production, the process avoids the use of antibiotics, chemical inducers, and mechanical disruption, while remaining compatible with standard infrastructure and low-cost adjuvants. Immunization of mice with an EIT-enriched periplasmic fraction (EIT-PF) induced strong antibody responses with enhanced functional activity against A/E pedestal formation in vitro , and accelerated clearance of experimental E. coli O157 infection in mice. A three-dose EIT-PF immunization was tested in cattle. Notably, a single EIT-PF dose elicited antibodies that recognized multiple EHEC serotypes and EPEC, as well as each chimera component, effectively interfering with T3SS-dependent pedestal formation in vitro . Our findings support EIT-PF as a broadly reactive, proof-of-concept vaccine candidate for cattle; further studies are required to assess efficacy under field conditions.